Formação e atuação de educadores ambientais : análise de um processo educativo na universidade - Leme, Patricia Cristina Silva (2008)
This research is part of a study on long term educational processes aimed at the training in environmental education. The investigation focused on the specialization course Education of Local Socio-environmental Sustainability Agents , offered by the University of São Paulo in 2003, with the objective of preparing university employees for environmental educational actions in their workplaces. The study analyzed the impact of the course on the employee s workplaces, according to the participants themselves, as well as the difficulties and conflicts experienced by the participants in their educational activities. The study also examined the conceptions of the environmental educator s role and tried to identify the elements, as perceived by the participants, that favored their preparation as environmental educators. Five participants were interviewed and another 18 answered a questionnaire. As complementary sources of information, class plans, written reports and evaluations and meeting records were used. The results of the study include the identification of the actions promoted by the employees in their workplaces, involving both educational and environmental management activities. The praxis, the creation of a learning community and the use of autobiographical reports were positive elements in the development of the employees as environmental educators. The main challenge faced by the local agents is to understand and to deal with political aspects of the institution and with the lack of a global environmental policy for the university.